How Motivation Influences Speaking Ability: A Study of Seventh-Grade Students at SMP Negeri 1 Ubud - Krisna, I Gusti Agung Hari; Krismayani, Ni Wayan; Kumara, Dewa Gede Agung Gana (PROJECT (Professional Journal of English Education), 2025)
The four primary English language skills are speaking, writing, listening, and reading. Speaking is the ability to express ideas, feelings, and thoughts verbally in various communication circumstances by using words. This study examines the relationship between speaking ability and motivation among seventh-grade students at SMP Negeri 1 Ubud. One hundred ten students from three classes were chosen by cluster sampling for the study, which used an ex post facto correlational research design. Speaking test to assess students' speaking abilities and questionnaires to gauge motivation were used to gather data. With a Pearson correlation coefficient of 0.377, the findings showed a strong and positive relationship between students' motivation and speaking abilities. This suggests a relationship that is meaningful but weak. According to the study, motivation is crucial in developing speaking skills. The results give teachers new perspectives on motivating students to acquire languages, especially in speaking. It also acts as a guide for future studies examining the connection between psychological variables and language learning.